Flexible Electronics - Rackauskas, Simas (IntechOpen, 2018)
The interest in flexible electronics is on the rise as it brings an added functionality and esthetic value in the unconventional interfaces, such as biomonitoring systems, wearables, flexible textiles, paper-based technologies, and many other curves of soft schemes, for which traditional electronics are not suitable. The demand in new flexible platforms turns to a pursuit for functional materials and technologies commonly compatible with a low temperature, high-throughput processing, and novel methods for device integration. A wide range of functional materials involving nanoparticles, composites, semiconductor and metallic nanowires, carbon nanomaterials, polymers, conductive inks, and different hybrid structures are particularly interesting. This book brings a comprehensive overview on the most important technology development in the field of flexible electronics.